Simultaneous Determination of 15 Mycotoxins in Aquaculture Feed by Liquid Chromatography–Tandem Mass Spectrometry - Beatriz Albero; María Luisa Fernández-Cruz; Rosa Ana Pérez (Toxins, 2022)
The use of plant-based fish feed may increase the risk of contamination by mycotoxins. The multiresidue analysis of mycotoxins in fish feed presents many difficulties due to the complexity of the matrix, the different characteristics of the compounds, and their presence in highly different concentration levels. The aim of this study was to develop a selective, sensitive, and efficient analytical method for the simultaneous determination of 15 mycotoxins (regulated and emerging mycotoxins) in aquaculture feed by LC-MS/MS. Sample extraction was performed with ultrasonic assistance, and different cleanup strategies were evaluated. The optimized method was composed by ultrasound-assisted extraction (two cycles, 55 °C, 20 min), followed by cleanup using a Captiva EMR Lipid cartridge. Then, nine commercial samples of aquaculture fish feed were analyzed. Eight of the 15 target mycotoxins were detected in the samples. Results showed that two enniatins (EENB and ENNB1), beauvericin, and fumonisin B2 were detected in all samples. These results show the multi-mycotoxin contamination of fish feed, highlighting the need to improve current knowledge on the occurrence and toxicity of mycotoxins in fish feed, mainly the emerging ones.